Hakekat Keadaan Darurat Negara (State Of Emergency) sebagai Dasar Pembentukan Peraturan Pemerintah Pengganti Undang-Undang - Muhammad Syarif Nuh Syarif Nuh (Jurnal Hukum IUS QUIA IUSTUM, 2011)
In issuing Perppu, president’s power seems to be “power full”, it can not get any intervention from any other institution until the trial in DPR decides whether the Perppu is approved or rejected. This research raises some problems; first, what is the measurement or basic of forming Perppu by President? Second, what is the substance and content of the state of emergency that leads the forced crisis? The research method is based on primary and secondary law material, and it is done through literature study and it used juridical approach method. The research result concludes, first, the measurement or basic of forming Perppu by president is based on the condition or event that is extraordinary (abnormal) from a state, in the form of the state of emergency. Second, the substance or content of the state of emergency that leads the forced crisis contains of three elements, which are, first, the element of dangerous threat; second, the element of reasonable necessity; and third, the element of limited time.Key words : State constitution, state of emergency, president’s power